2016
DOI: 10.1007/s11230-016-9631-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular approaches to trematode systematics: ‘best practice’ and implications for future study

Abstract: 'Molecular approaches to trematode systematics: 'best practice' and implications for future study ', Systematic Parasitology, 93(3), 295-306. The final publication is available at Springer via http://dx.doi.org/10.1007/s11230-016-9631-2.The full details of the published version of the article are as follows: However, since the late-1980s we have seen an increased integration of genetic data to overcome problems encountered when morphological data are considered in isolation. Here, we provide advice regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
98
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(99 citation statements)
references
References 85 publications
0
98
0
1
Order By: Relevance
“…In this group, the trend is to use a combination of molecular markers since half of the 64 cryptic species reports used both nuclear and mitochondrial markers to detect cryptic species. Just for trematodes, Blasco-Costa et al (2016) recently found that in the past 5 years most of the studies focusing on taxonomy, diversity, phylogeny and life cycles that generated mitochondrial sequences also reported nuclear DNA sequences. Actually, Blasco-Costa et al (2016) argued that the best practice for the discipline would be to obtain sequence data from at least two independently evolving or unlinked loci, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In this group, the trend is to use a combination of molecular markers since half of the 64 cryptic species reports used both nuclear and mitochondrial markers to detect cryptic species. Just for trematodes, Blasco-Costa et al (2016) recently found that in the past 5 years most of the studies focusing on taxonomy, diversity, phylogeny and life cycles that generated mitochondrial sequences also reported nuclear DNA sequences. Actually, Blasco-Costa et al (2016) argued that the best practice for the discipline would be to obtain sequence data from at least two independently evolving or unlinked loci, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, the question of to which, if any, of the existing named species the five unnamed taxa can be identified is exceptionally problematic, given the issues identified by Bray & Gibson[39], Bray[16] and others -morphological plasticity, uncertainty regarding the extent to which species may be widespread and the reliability of their patterns of host-specificity. The ultimate solution to these issues can only lie in further study, ideally in the form of combined morphological and molecular analyses incorporating multiple biomarkers[41]. Studies that examine material from type-hosts and type-localities of existing species will be especially important.…”
mentioning
confidence: 99%
“…A fragment of the internal transcribed spacer 2 region (ITS2) was chosen for analyses because this region has been proven to be a reliable marker and has been commonly used to identify digenean species (Esteban et al 2014, Blasco-Costa et al 2016, Chai 2019. Total genomic DNA was extracted from cercariae isolated from infected snails using the Dneasy Blood and Tissue Kit (QIAGEN, Hilden, Germany).…”
Section: Molecular Analysesmentioning
confidence: 99%
“…Generally, it is possible to identify cercarial specimens to the family level, and occasionally to the genus level, using morphological criteria, but it is not easy to differentiate cercariae of related genera/species based on their morphology alone (Frandsen and Christensen 1984). Alternatively, molecular techniques have been used to support the morphological identification (e.g., Bartoli et al 2000, Pina et al 2007, Chuboon and Wongsawad 2009, Kudlai et al 2015, Blasco-Costa et al 2016, Chontananarth et al 2017, Doanh et al 2018.…”
mentioning
confidence: 99%